A Principle of Designing Game-Based Learning for Speaking Skills - Nanang Triasmosari (Syntax Idea)
Microsoft Office Translator MAKE IT, a principle of designing simple game-based learning for speaking skills. Effective learning can be achieved when the learning process feels good to students. Learning something fun keeps people unencumbered. On the contrary, learning something that you don't like, besides being boring quickly, the result is not maximum. On the basis of that assumption, teachers need to design teaching strategies that make students love the learning process. Of course, this job is not an easy thing. This is a concrete and phenomenal teacher professional challenge. Students love learning so that the learning process becomes fun is the hope of all teachers. MAKE IT is a set of principles in designing simple game-based learning to answer these challenges. MAKE IT that offers simple learning design; Fun, Active, Communicative, Economic, Interractive and Integrated have proven to be able to: (1) foster pleasure, (2) increase activeness, (3) foster confidence to communicate verbally, (4) make learning media simple and inexpensive, (5) train togetherness, and (6) activate the use of more body senses to learn language in a total and optimal way. The set of principles of MAKE IT in game design in learning is as follows: (1) Fun (Fun), which is to offer fun because it is game-based so that learning becomes more effective, (2) Active (Active), which is to foster student activity in learning because they will be 'forced' to speak following the game provided, (3) Communicative (Communicative), which is to cultivate confidence to communicate with their colleagues in the game by prioritizing 'peer correction', (4) Economical, which is a learning medium using simple technology that is easy to make and cheap, even a recycled material 'garbage', (5) Interactive (Interractive), which is the togetherness that is put forward in language training, (6) Integrated (Integrated), which is the full use of the body senses in learning language so as to produce better long-term memory Microsoft Office Translator MAKE IT, a principle of designing simple game-based learning for speaking skills. Effective learning can be achieved when the learning process feels good to students. Learning something fun keeps people unencumbered. On the contrary, learning something that you don't like, besides being boring quickly, the result is not maximum. On the basis of that assumption, teachers need to design teaching strategies that make students love the learning process. Of course, this job is not an easy thing. This is a concrete and phenomenal teacher professional challenge. Students love learning so that the learning process becomes fun is the hope of all teachers. MAKE IT is a set of principles in designing simple game-based learning to answer these challenges. MAKE IT that offers simple learning design; Fun, Active, Communicative, Economic, Interractive and Integrated have proven to be able to: (1) foster pleasure, (2) increase activeness, (3) foster confidence to communicate verbally, (4) make learning media simple and inexpensive, (5) train togetherness, and (6) activate the use of more body senses to learn language in a total and optimal way. The set of principles of MAKE IT in game design in learning is as follows: (1) Fun (Fun), which is to offer fun because it is game-based so that learning becomes more effective, (2) Active (Active), which is to foster student activity in learning because they will be 'forced' to speak following the game provided, (3) Communicative (Communicative), which is to cultivate confidence to communicate with their colleagues in the game by prioritizing 'peer correction', (4) Economical, which is a learning medium using simple technology that is easy to make and cheap, even a recycled material 'garbage', (5) Interactive (Interractive), which is the togetherness that is put forward in language training, (6) Integrated (Integrated), which is the full use of the body senses in learning language so as to produce better long-term memory